Sakera Application as an Effort to Assess Mental Health and Self-Potential in Adolescents - Fakhriyani, Diana Vidya; Fitriyah, Lailatul; Laily, Nurul; Hasby, Khoirul Umam (Program Studi Bimbingan dan Konseling Islam, 2025)
Mental health problems can be an obstacle to achieving psychological well-being. Mental health problems are susceptible to being experienced by anyone, including teenagers. Teenagers tend to be unable to understand their mental health condition and potential. The aim of this research is to find out: the creation and development of the SAKERA (Self-care, Knowing Excellent Potential and Realizing Dreams) application, teenagers' response (interest) in the Sakera application, and use of the Sakera application to help identify mental health problems and personal potential in adolescents. This research is research and development (R&D). The subjects in the research were 17 students at MA Al-Djufri Pamekasan. The results of this research and development show that, first, the Sakera application is